2017
DOI: 10.1002/csr.1473
|View full text |Cite
|
Sign up to set email alerts
|

External Pressures or Internal Governance – What Determines the Extent of Corporate Responses to Climate Change?

Abstract: To prevent adverse effects from climate change, it is vital to involve the private sector in mitigation efforts. So far, however, research has insufficiently addressed the determinants of corporate action in specific industries. Our paper aims at bridging this gap by empirically analyzing the global automotive industry's response to climate change mitigation issues. We use publicly available information from 105 sector leaders to investigate the role of external institutional pressures and intra-organizational… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
33
1
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 52 publications
(37 citation statements)
references
References 58 publications
(107 reference statements)
2
33
1
1
Order By: Relevance
“…The results provide diverse contributions to the literature on antecedents of climate action. Research has indeed focused on institutional and organizational antecedents, such as regulatory pressures (Damert & Baumgartner, 2018), resource endowments (Escobar & Vredenburg, 2011) and capabilities (Lee & Klassen, 2016). Similar studies draw from institutional theory and resource‐based view to identify external and internal constraints (e.g., regulations, resources and routine) that define feasible and appropriate organizational responses.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The results provide diverse contributions to the literature on antecedents of climate action. Research has indeed focused on institutional and organizational antecedents, such as regulatory pressures (Damert & Baumgartner, 2018), resource endowments (Escobar & Vredenburg, 2011) and capabilities (Lee & Klassen, 2016). Similar studies draw from institutional theory and resource‐based view to identify external and internal constraints (e.g., regulations, resources and routine) that define feasible and appropriate organizational responses.…”
Section: Discussionmentioning
confidence: 99%
“…Drawing insights from the emerging literature on climate inaction and from corporate sustainability literature, the present study investigates antecedents of corporate responses to climate change by focusing on managerial factors. Although previous studies have investigated pressures at the organizational and institutional levels that contribute to shape corporate responses to climate change (Cadez, Czerny, & Letmathe, 2019; Damert & Baumgartner, 2018; Lee & Klassen, 2016; Lopes de Sousa Jabbour, Vazquez‐Brust, Chiappetta Jabbour, & Andriani Ribeiro, 2020), current understanding of the managerial antecedents of climate action is partial. Research has delved into the regulatory, competitive and societal pressures towards corporate engagement with climate issues, while overlooking the managerial factors that drive companies to embrace pressures towards climate action and resist motives for inaction (Daddi, Todaro, de Giacomo, & Frey, 2018).…”
Section: Introductionmentioning
confidence: 99%
“…An investigation to identify engaged behaviour has resulted in a focus on external stakeholder engagement. Damert and Baumgartner () study of climate change strategies about the automotive industry illustrates low centrality and high salience in an engaged organisation. The authors found that corporate climate action is rather linked to reputational concerns than to compliance issues.…”
Section: Types Of Carbon Disclosure Strategiesmentioning
confidence: 99%
“…Due to the higher use of the Internet and social networks of late, companies are more frequently exposure and judged on the basis of their environmental stewardship and business practices [57]. Companies with business activities that necessitate interaction with the end consumer tend to be most active [58]; however, together with other parties, including labor union and environmental NGO groups, media and social networks and customersy achieved a moderate score of 3 points or less due to probably small portion of samples companies with the product type of final goods, implying that these bodies had little effect on a company's carbon strategy efforts. …”
Section: Determinant Factors For Carbon Management In Korean Companiesmentioning
confidence: 99%